2004
DOI: 10.1889/1.1811457
|View full text |Cite
|
Sign up to set email alerts
|

6.2: Lifetime of Single Panel LCOS Imagers

Abstract: The lifetime of the TN45 effect used in single panel LCOS imagers has been demonstrated to be 20,000 hours at 2 Mlux illumination. This paper will document the test methods used to determine this lifetime. The variation in lifetime under different illumination conditions will also be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…For an LC material/alignment layer at a given wavelength, the degradation mechanism is not a linear function of the employed light intensity. 14 The higher intensity is more harmful than the low intensity even though their total UV dosage (intensity multiplied by exposure time) remains the same. To obtain a realistic result, in principle, we should measure the lifetime at several intensities, fit the data, and extrapolate back to the intensity of the actual LCD projector.…”
Section: Discussionmentioning
confidence: 99%
“…For an LC material/alignment layer at a given wavelength, the degradation mechanism is not a linear function of the employed light intensity. 14 The higher intensity is more harmful than the low intensity even though their total UV dosage (intensity multiplied by exposure time) remains the same. To obtain a realistic result, in principle, we should measure the lifetime at several intensities, fit the data, and extrapolate back to the intensity of the actual LCD projector.…”
Section: Discussionmentioning
confidence: 99%
“…Cells that showed uniform LC alignment and a pre-tilt between 3°and 5°were subjected to accelerated lifetime tests. 1 Accelerated lifetime tests showed that the lifetime of LCOS microdisplays with ion-milled DLC layers was a factor 0.5-0.7 shorter than the lifetime of LCOS microdisplays with conventional rubbed PI alignment layers. NEXAFS experiments (see next paragraph) showed that C = C bonds are broken during the ion-milling process.…”
Section: Lifetime Of Lcos Microdisplays With Ion-milled Dlc Alignmentmentioning
confidence: 98%
“…Experimental data have shown that Philips LMS imagers exceed the 20,000-hour lifetime requirement under 2.0 Mlux of illumination. 1 Due to future miniaturization of the LCOS microdisplay, the light load on the display will increase. High light fluxes will decompose several components of the microdisplay and will therefore reduce the lifetime of the panel.…”
Section: Introductionmentioning
confidence: 99%
“…XPS also revealed the important role of LC remnants (polymerized LC) in the loss of alignment and helped to understand better the mechanism of alignment degradation in LCOS cells. Further work 3,4 was dedicated to electro-optic studies. Wen 3 presented extensive experimental data about the degradation of electro-optic parameters and alignment of two LC mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 4, the primary focus was the methods of panel lifetime testing and the lifetime dependency on the light intensity and UV-cutoff wavelength.…”
Section: Introductionmentioning
confidence: 99%